The Public health problem and resistant bacteria in lowand middle-income countries - IACONI, Oana-Simina; FERDOHLEB, Alina; BALAN, Greta; GALBEN, Lucia; DZIEWIT, Lukasz; BORREGO, Carles M. (One Health & Risk Management, 2023)
Introduction. Antimicrobial resistance has been declared a major public health problem. As a result of excesive antibiotic usage, it became an environmental issue. This problem is now more visible in Low-and Middle-Income Countries, where it increases the social burden. One of the newest methods to fight antimicrobial-resistant bacteria (ARB) is by using bacteriophages.Aim Identification and characterization of possible phage targets from waterland.Material and methods The strains were obtained from inpatients and identified using VITEK 2 Compact and culture. The resistance profiles were determined by disk diffusion method and interpreted according to EUCAST metodology. The presence of resistance mechanisms was checked by phenotypic testing. 31 bacterial strains were selected for research.Results K. pneumoniae, P. aeruginosa, Acinetobacter spp., S. aureus, E. coli and Enterococcus spp. were identified. The resistance profile of the isolates showed: 61,5% of K. pneumoniae isolates were PDR, and 23,1% were susceptible only to Carbapenems. E. coli strains were XDR, 71,4% of P. aeruginosa and 75% of Acinetobacter spp. were PDR bacteria. The susceptibility profile of S. aureus strains showed that 3/4 were resistant to Cephalosporins and Fluoroquinolones.Conclusions Combating the AMR phenomenon starts with knowing the pathogens present in the environment. This study is the cornerstone for further research that will ultimately lead to finding suitable phages for water treatment in Moldova, hoping they will reduce the economic and social burden and also, environmental contamination.